2022
DOI: 10.1055/s-0042-1745740
|View full text |Cite
|
Sign up to set email alerts
|

Management of Pathologic Fractures around the Knee: Part 1—Distal Femur

Abstract: Pathologic fractures secondary to metastatic disease are an increasingly prevalent problem. Such patients require multidisciplinary collaboration to optimize clinical outcomes. An established algorithm for clinical, laboratory, and radiographic work-up will ensure that each patient achieves the best outcome while avoiding catastrophic complications. Metastatic disease to the region of the knee is less commonly encountered than in other regions of the body, but it presents unique difficulties that merit discuss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 80 publications
0
0
0
Order By: Relevance
“…According to a large retrospective database study done by Willeumier et al, approximately 10% of all femoral metastases were located distally [2]. While there are many potential surgical treatments including endoprosthetic reconstruction, plate fixation, intramedullary nail fixation, and arthroplasty, the choice of surgical fixation is often based on clinical experience given the scarcity of literature regarding treatment of distal femoral pathologic fractures [6][7][8][9]. In a systematic review by Willeumier et al, only two studies were found that reported outcomes specific to this fracture type [6].…”
Section: Discussionmentioning
confidence: 99%
“…According to a large retrospective database study done by Willeumier et al, approximately 10% of all femoral metastases were located distally [2]. While there are many potential surgical treatments including endoprosthetic reconstruction, plate fixation, intramedullary nail fixation, and arthroplasty, the choice of surgical fixation is often based on clinical experience given the scarcity of literature regarding treatment of distal femoral pathologic fractures [6][7][8][9]. In a systematic review by Willeumier et al, only two studies were found that reported outcomes specific to this fracture type [6].…”
Section: Discussionmentioning
confidence: 99%